Identifying leverage points to promote women’s economic resilience to climate change challenges in Tanzania – Fish value chain - Kilanga, Lucyphine; Kakwasha, Keagan; Kitogo, Lawrence; Simbila, Deogratius; Muzungaire, Lizzy; Lukanga, Editrudith; Mudege, Netsayi (WorldFish, 2024)
The goal of HER+ is to build the economic resilience of women to climate change challenges in agri-food systems (AFS) through gender equality and social inclusion. In February 2023, the HER+ team studied how gender norms constrain women’s economic resilience to climate change challenges among fisherfolk in Muleba district of Kagera region in Tanzania. Following the completion of the study, WorldFish and AWFISHNET Tanzania Chapter (TAWFA) and Environmental Management and Economic Development Organization (EMEDO) partnered to disseminate and validate research findings and identify leverage points to transform gender norms and make women economically resilient to the impacts of climate change in the fisheries value chain.